A diagnostic study of target language speaking problems. Case of: Advanced intensive english I, Intermediate intensive english I and Readings and conversation I students at the Foreign Languages Department, UES, semester II, 2015 - Ángel Avalos, Evelin Patricia
In today‟s world, learning English as a second language has become an important and useful tool due to the fact that opens many doors to different cultures and job fields that demand mastering the four language skills (listening, reading, speaking and writing) which are crucial to obtain all the necessary knowledge to become competent and proficient in the language. However, many English as a foreign language learners‟ face many obstacles during their learning process mainly in the speaking area. There are several oral communication problems that learners are facing nowadays, for instance: Interference of mother tongue (L1), lack of vocabulary knowledge, grammar as a stumbling block, inadequate pronunciation and intonation, few opportunities to speak English in class, lack of exposure to the target language, poor input environment for spoken communication outside the class, among others. As a result of these problems, many of them do not achieve a satisfactory level of communicative competence. This level is ultimately achieved when the learner masters a set of sub skills in regards to speaking. Some of these sub-skills are pronunciation, intonation, accuracy and fluency that will help them to overcome oral communication problems in the target language. This research aims to identify the different oral communication problems students of a second language are facing in the Intermediate Intensive English I, Advanced Intensive English I and Readings and Conversation I courses during the semester II, 2015, in order to propose possible strategies, methodologies and techniques, to overcome them as a way for improving the quality of their oral proficiency in the target language.